2019
DOI: 10.1038/s41598-019-44402-0
|View full text |Cite
|
Sign up to set email alerts
|

New PCR primers for metabarcoding environmental DNA from freshwater eels, genus Anguilla

Abstract: Freshwater eels of the genus Anguilla comprise 16 species that include three subspecies and are characterized by their unique catadromous life cycles. Their life histories and nocturnal life styles make it difficult to observe them in freshwater and marine habitats. To investigate their distribution and ecology in aquatic environments, we developed new PCR primers for metabarcoding environmental DNA (eDNA) from Anguilla . The new primers (MiEel) were designed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…The primers and probe designed for this study were able to detect eDNA of A. anguilla origin in all five freshwater Irish lakes. Although the detection of A. anguilla eDNA has been previously reported in single species and metabarcoding detection studies (Seymour et al, 2018;Takeuchi et al, 2019;Thomsen, Kielgast, Iversen, Møller, et al, 2012), it was not applied for field monitoring. There is significant homology between the mtDNA of A. anguilla and A. rostrata-its and A. rostrata sourced from N. America confirmed the specificity of these primers and did not amplify using the primer-probe set (Table S1).…”
Section: The Detection Of Anguilla Anguilla Edna In Freshwater Lakesmentioning
confidence: 99%
“…The primers and probe designed for this study were able to detect eDNA of A. anguilla origin in all five freshwater Irish lakes. Although the detection of A. anguilla eDNA has been previously reported in single species and metabarcoding detection studies (Seymour et al, 2018;Takeuchi et al, 2019;Thomsen, Kielgast, Iversen, Møller, et al, 2012), it was not applied for field monitoring. There is significant homology between the mtDNA of A. anguilla and A. rostrata-its and A. rostrata sourced from N. America confirmed the specificity of these primers and did not amplify using the primer-probe set (Table S1).…”
Section: The Detection Of Anguilla Anguilla Edna In Freshwater Lakesmentioning
confidence: 99%
“…Indeed, although recent studies (Bylemans et al 2018a;Collins et al 2019;Zhang et al 2020) have demonstrated that MiFish primers outperformed other competing primers, primer/ template mismatches in MiFish primers occasionally cause underrepresentation of some fish groups (Fig. 7), and MiFish sequences often lack interspecific variations among some closely related congeners, most notably among commercially important groups, such as tunas , salmons (Morita et al 2019), and freshwater eels (Takeuchi et al 2019). However, these technical problems can be alleviated by the optimization of MiFish primers to local fauna and by simultaneous use of universal MiFish primers and newly developed group-specific primers amplifying more variable regions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the freshwater eel genus Anguilla also showed a lack of interspecific variations, and Takeuchi et al (2019) designed a new primer pair (MiEel) on the mitochondrial ATP6 gene with reference to the aligned mitogenome sequences from 16 constituent species. The new primer pair amplifies a variable region with sufficient interspecific variations (5-22 nucleotide differences and 1-3 nucleotide differences between three subspecies pairs), and preliminary experiments using natural waters from two rivers successfully detected Japanese freshwater eel Anguilla japonica using multiplex PCR with MiFish-U (Takeuchi et al 2019). Takeuchi et al (2019) argue that the MiEel metabarcoding would be particularly effective for documenting species distributions and for surveying spawning grounds where co-occurrence of multiple Anguilla species might be expected.…”
Section: Taxonomic Optimization Of the Primersmentioning
confidence: 97%
See 2 more Smart Citations